Applications in Household-economic Archaeology - Ringstedt, Nils (Current Swedish Archaeology, 1994)
Household-economic considerations should be used in archaeology in order to elucidate the living conditions within a region. Consumer behaviour, socio-economic status and male/female activities have been surveyed by using relative "grave values" and frequency values based on material from cemeteries on Bornholm and Lovön and from the Genesmon settlement in northern Ångermanland. Future work is suggested regarding the gravegoods in the Birka graves and the artifacts from the recently excavated Valsta, Fresta and Sanda settlements.